1996
DOI: 10.1007/bf00176189
|View full text |Cite
|
Sign up to set email alerts
|

DNA ploidy, S-phase, and Ki-67 antigen expression in the evaluation of cell content of pleural effusions

Abstract: Cells from pleural effusions (28 malignant and 14 nonmalignant with reactive mesothelial cells) were examined in parallel by means of conventional cytology and multiparametric flow cytometry. The latter included the evaluation of DNA ploidy, the calculation of DNA index (DI), the determination of S phase fraction (SPF), and cell proliferation associated with Ki-67 antigen expression. Propidium iodide was used for the DNA staining, and fluorescein-conjugated monoclonal mouse antibodies were applied to the human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Percentage values of Ki-67 determination were dichotomized on subgroups showing !20% and 120% of positive cells. This cut-off resulted from our previous studies [13]. We found there that in nonmalignant pleural effusions the proportion of Ki-67-positive cells did not exceed 20% (corresponding to a specificity of 100%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percentage values of Ki-67 determination were dichotomized on subgroups showing !20% and 120% of positive cells. This cut-off resulted from our previous studies [13]. We found there that in nonmalignant pleural effusions the proportion of Ki-67-positive cells did not exceed 20% (corresponding to a specificity of 100%).…”
Section: Discussionmentioning
confidence: 99%
“…An example of immunologically active cells being in direct contact with a tumor are cells from malignant pleural effusions. In the previous study we have evaluated DNA ploidy, S phase fraction, Ki-67 antigen expression [13] and AgNORs number [14] in the cells of pleural effusions. We concluded that the cells of malignant and benign pleural effusions show differences concerning these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Saleh et al 9 studied Ki-67 (MIB1) immunostaining with microwave antigen retrieval on cell block sections of serous effusions and reported a significant difference in the mean Ki-67 value between malignant (28%) and benign (9%) effusions. Sikora et al 10 studied Ki-67 expression in serous effusions with flow cytometry using fluorescein-conjugated antibody.…”
Section: Acta Cytologicamentioning
confidence: 99%
“…8 Only a few of these antibodies have been investigated in effusion cytology. [9][10][11] RNR is a key enzyme in the synthesis of deoxyribonucleotide from ribonucleotides. 12 This enzyme is composed of two nonidentical subunits, R1 and R2, which are differentially regulated during the cell cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation